The value of wild edible plants among rural communities in Chlef province (Algeria): A quantitative ethnobotanical survey: Wild edible plants in Chlef province - Merouane, Abdelaziz; Cheurfa, Mohammed; Noui, Abdallah; Benbeskri, Aicha (Ethnobotany Research and Applications, 2025)
Background: Traditional knowledge of wild edible plants (WEPs), which play a significant role in the dietary and cultural traditions of rural communities worldwide, has shown a worrying decline over recent decades. This research investigates the diversity, traditional uses, and cultural significance of wild edible plants in the rural community of Chlef Province, Northwest Algeria, aiming to document and analyze indigenous knowledge. Methods: Data were collected between March and April 2023 through semi-structured interviews with 100 informants (68 female, 32 male) aged 20–70. Taxonomic identification of plants was performed, and the relative frequency of citation (RFC), frequency of citation (FC), and standardized weight index of families (SWIf) were calculated. Growth habits, plant parts used, and preparation methods were analyzed alongside cultural practices related to WEPs. Results: The study identified 51 species of WEPs belonging to 25 families, with Lamiaceae (22%) and Asteraceae (18%) being the most represented. Aerial parts, leaves, and fruiting parts were the most commonly utilized, consumed primarily raw, cooked, or as herbal teas. Culturally significant species included Malva sylvestris L. (FC = 7.45%), Scolymus hispanicus L. (FC = 6.86%), Cynara cardunculus L. (FC = 6.56%), Spinacia oleracea L. (FC = 5.96%), Quercus ilex L. (FC = 5.89%), Ceratonia siliqua L. (FC = 5.66%), and Laurus nobilis L. (FC = 5.66%). The RFC index was not affected by plant parts or growth habits. The highest SWIf values were attributed to Malvaceae (1), Asteraceae (0.99), Fagaceae (0.79), and Fabaceae (0.76). Conclusions: Despite the decline in traditional knowledge, WEPs remain integral to the local diet, valued for their unique flavors, health benefits, and historical importance. Efforts to conserve and promote these natural resources are essential for preserving the region's culinary heritage and biodiversity. Keywords: Sustainable utilization, Gastronomic heritage, Biodiversity conservation, Natural resources